Bank foreign affiliate performance in the face of pervasive and arbitrary corruption - Petrou, Andreas (My University, 2014)
This study investigates the financial performance of foreign bank affiliates in light of their experience with pervasive and arbitrary corruption. To achieve this, we draw on the resource dependence theory and the institutional theory to explain how pervasiveness and arbitrariness affect financial performance through operating costs, risks of defaults and business growth. Using data on 122 foreign bank affiliates in 37 countries, we find that pervasiveness has a negative influence on the affiliate's performance, and, the joint interaction of pervasiveness and arbitrariness strengthens this relationship. The latter is significant for affiliates operating in developing countries, which may indicate that arbitrariness is damaging when corruption is pervasive. This study advances the literature on corruption at firm-level, and the literature on bank internationalization. Moreover, findings have implications for managers, who need to recognize how the interaction of these two dimensions of corruption compromise their foreign operations.
Keywords: Arbitrariness; Banking; Corruption; Foreign affiliates; Performance; Pervasiveness